Образование и подготовка специалистов в области сварки и испытания материалов - Кайтель, С.; Аренс, С. (Автоматическая сварка, 2008)
The education according to the IIW system which is internationally approved is the striking example of reorganization and harmonization of national and international standards on the personnel qualification. The preparation technique is continuously improving through the teaching conceptions which are supported by multimedia and Internet. Ever more complicated multimedia technologies require opportunities of similar teaching of qualified personnel also in the field of testing technology.